Screening for microalgae strains containing lipid in some places in Southern Vietnam - My Lan, Nguyen Thi; Ngoc Phuong, Nguyen Hoang; Hung, Huynh Hiep; Thang, Nguyen Tien; Thanh Loan, Le Thi; Mong Tham, Doan Thi; Ho, Pham Thanh; My Phuoc, Le Thi (Academia Journal of Biology, 2013)
Microalgal biodiesel is considered as an alternative to fossil fuel and also potentially reduce the introduction of new CO2 by displacing fossil hydrocarbon fuels. Nowadays, researching on renewable energy is mainly focused on biodiesel from microalgae due to their fast growth rates and high-yield production. In order to improve this field in Vietnam, we isolated some local species and used rapid screening method for lipid production in microalgae based on Nile Red fluorescence. In this study we determined 6 microalgae strains namely Pediastrum duplex Meyen, Asterococcus limneticus G. M. Smith, Coelastrum cambricum Archer, Cosmarium cf. sumatranum Krieger, Scenedesmus ellipsoideus Chodat and Scenedesmus acuminatus (Lag.) Chodat containing lipid from freshwater samples from ponds and lakes and 10 strains viz Amphora sp., Chaetoceros sp., Nitzschia sp., Chlamydomonas sp., Cyanodictyon cf. endophyticum Pascher, Dunaliella sp., Chloridella sp., Nannochloropsis sp., Fernandinella sp. and Tetraselmis sp. from salt-water samples at salterns, shrimp ponds and seas.